Energy Productivity and Green Energy Productivity in India: Do they Follow the Same Trend? - Prasad, Mousami; Bhattacharya, Poulomi (Productivity: A Quarterly Journal of The National Productivity Council, 2025)
Balancing emissions and economic growth is central to India's energy and climate policy. Energy productivity is a useful frame for energy policy planning. The present study investigates the factors driving it, particularly efficiency. The study also analy
Keywords: Climate Policy; Energy Consumption; Energy Productivity; Green Energy Productivity; Economic Growth